Dinuclear ruthenium sawhorse-type complexes containing bridging ligands with ferrocenyl substituents in endo/endo, endo/exo and exo/exo orientations - Auzias, Mathieu; Therrien, Bruno; Labat, Gael; Stoeckli-Evans, Helen; Süss-Fink, Georg (My University, 2006)
The dinuclear Ru complexes Ru2(CO)4(OOCC5H4FeC5H5)2L2 (L = py: 1, L = PPh3: 2) were synthesized from Ru3(CO)12, ferrocene carboxylic acid and pyridine or PPh3, resp. The single-crystal x-ray structure anal. reveals for 1 and 2 a Ru2(CO)4 sawhorse backbone with the two ferrocenyl substituents of the two carboxylato bridges being endo/exo with respect to each other in the solid state. With the new pyridine deriv. NC5H4OOCC5H4FeC5H5-4 (4-ferrocenoyloxypyridine) (3) as axial ligand, the complex Ru2(CO)4(OOCC5H4FeC5H5)2(NC5H4OOCC5H4FeC5H5-4)2 (4) was obtained, the single crystal x-ray structure anal. showing an exo/exo orientation of the two carboxylato bridges in the solid state. The endo/endo orientation is found in the solid-state structure of Ru2(CO)4(HNOCC5H4FeC5H5)2(PPh3)2 (5), the two OCNH bridges being transoid with respect to each other; this complex is accessible from Ru3(CO)12, ferrocenamide and PPh3. [on SciFinder(R)]
Keywords: ruthenium carbonyl pyridine phosphine ferrocenecarboxylate complex prepn structure; ferrocenoylpyridine prepn complexation ruthenium; carbonyl iron ferrocenoyloxypyridine complex prepn structure; crystal structure iron ferrocenoylpyridine ferrocenecarboxylate ferrocenamide carbonyl complex; ferrocenamide ruthenium carbonyl phosphine complex prepn structure